A verbal descriptor incremental pain scale developed by South African Tswana-speaking patients with low back pain - Michelle Yazbek; Aimee V. Stewart; Alison Bentley (AOSIS, 2018)
Background: Measuring pain in patients whose home language is not English can be difficult as there may not be a scale available in their home language. Scales devised in other countries may also not be accurate after translation. Objectives: The aim of this study was to develop and test a new verbal pain descriptor scale in a Tswana-speaking population in South Africa with low back pain. Method: Two separate Tswana-speaking groups (20 males and 20 females) of patients with low back pain were asked to describe each of four categories of pain: mild, moderate, severe and worst. They then voted and descriptions obtaining more than 70% of the vote were taken to the next round of voting with both groups together. A final scale of one description for each category of pain (Tswana Verbal Pain Descriptor Scale - TVPDS) for both males and females was tested on a sample of 250 patients with low back pain and against three other non-verbal pain scales. Results: All items on the final scale were approved by at least 70% of both male and female participants. The scores for the TVPDS correlated well with present pain perception (r = 0.729, p < 0.0001) measured on the numerical visual analogue scale. The TVPDS correlated well with the Wong-Baker FACES Pain Rating Scale (r = 0.695, p < 0.0001) and the Pakistani Coin Pain Scale (r = 0.717, p < 0.0001). Conclusion: The TVPDS has the potential to be a useful clinical scale but more testing in other languages is still required. Clinical implications: This pain scale has the potential to be a useful scale to use for Tswana-speaking persons with low back pain and could also be useful for persons of other languages, if translated.